Means medical physical culture in rehabilitation of children with bronchial asthma in a sanatorium - Полковник-Маркова [Polkovnik-Markova V.], В. С. (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> describes the current issue of increasing incidence of asthma, including children, considering that bronchial asthma can lead to disability. Described risk factors for the disease in childhood.Emphasized the need for rehabilitation measures for this category of patients.Characterized methodological approaches to the use of medical physical training with bronchial asthma.Paid special attention to the peculiarities of making complex medical gymnastics andcarrying out of employment, based on the specifics of working with children. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->